1996
DOI: 10.1172/jci118440
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced exocytosis of endothelial cell Weibel-Palade bodies. A mechanism for rapid neutrophil recruitment after cardiac preservation.

Abstract: The period of hypoxia is an important priming event for the vascular dysfunction that accompanies reperfusion, with endothelial cells (ECs) and neutrophils (PMNs) playing a central role. We hypothesized that EC Weibel-Palade (WP) body exocytosis during the hypoxic/ischemic period during organ preservation permits brisk PMN recruitment into postischemic tissue, a process further amplified in an oxidant-rich milieu. Exposure of human umbilical vein ECs to a hypoxic environment (pO 2 ഠ 20 torr) stimulated release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
2
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(161 citation statements)
references
References 57 publications
7
149
2
3
Order By: Relevance
“…It has been shown that hypoxia per se activates exocytosis of WPB 14 (although UA levels were not determined), the event that may take place within the ischemic organ. Distant regulation of exocytosis of WPB can be accomplished, according to the data presented here, via release of the product of xanthine oxidase activation in the ischemic organ-UA.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that hypoxia per se activates exocytosis of WPB 14 (although UA levels were not determined), the event that may take place within the ischemic organ. Distant regulation of exocytosis of WPB can be accomplished, according to the data presented here, via release of the product of xanthine oxidase activation in the ischemic organ-UA.…”
Section: Discussionmentioning
confidence: 98%
“…A list of compounds known to induce exocytosis of WPB is long and includes thrombin, histamine, peptido-leukotrienes, complement components, superoxide anion, VEGF, sphingosine-1-phosphate, ceramide, purine nucleotides, serotonin, vasopressin, and epinephrine (15, 21, 9). Notably, ischemia-reperfusion injury to various organs has been shown to release WPB (14,20).The possibility of exacerbated tissue injury and inflammation as a result of exocytosis of WPB has been explored in several studies. Matsushita et al (16) developed fusion polypeptides composed of a 22-amino acid N-ethyl-maleimidesensitive factor (a regulator of exocytosis) and a carrier peptide derived from the human immunodeficiency virus transactivating regulatory protein domain and demonstrated that inhibition of WPB exocytosis decreased leukocyte trafficking and peritonitis (7).…”
mentioning
confidence: 99%
“…A list of compounds known to induce exocytosis of WPB is long and includes thrombin, histamine, peptido-leukotrienes, complement components, superoxide anion, VEGF, sphingosine-1-phosphate, ceramide, purine nucleotides, serotonin, vasopressin, and epinephrine (15, 21, 9). Notably, ischemia-reperfusion injury to various organs has been shown to release WPB (14,20).…”
mentioning
confidence: 99%
“…An example of this principle is the critical period during organ preservation, when hypoxemia and stasis prime the graft vasculature for damage during reperfusion. 15 Such tissue injury occurring as soon as blood flow to the graft is reestablished is limited by strategies to diminish preservation-induced vascular dysfunction with more optimal preservation solutions during the period of organ storage. Our brief review will focus on mechanisms through which hypoxemia promotes fibrin formation in vivo and the results of recent studies to elucidate the bases for such activation of the procoagulant pathway.…”
mentioning
confidence: 99%